Assessment method of distribution network health level based on multivariate information - Zhu, Lin; Wu, Zilong; Huang, Shiyu (Frontiers in Energy Research, 2023)
In order to enhance self-monitoring and self-diagnosis capabilities in smart distribution networks, this paper proposes a method for assessing the health level of the network based on multivariate information. First, we construct an evaluation indicator system for the health of the smart distribution network by integrating the smart distribution network information system. Next, we utilize the improved BP neural network and multivariate indicator information to calculate the health indexes of both grid layer and equipments. We then solve the health index of the equipment layer based on network topology and goal-oriented methodology. Furthermore, by utilizing the health information of both the equipment and grid layer, we apply fuzzy evaluation and D-S evidence theory to obtain the health level of the distribution network, which provides a comprehensive evaluation of the overall health status of the smart distribution network. Finally, we validate the proposed method using data from a regional distribution network, and the results demonstrate the effectiveness of the method. This method has the potential to improve the overall health and stability of smart distribution networks by enabling more effective self-monitoring and self-diagnosis.